Analysis of the Curative Effect of Alexandrite Laser in the Treatment of Venous Lake of Lips. Issue 7 (25th November 2020) - Wang, Zhihan; Ke, Chen; Yang, Ming; Lai, Min; Qi, Nian; Ke, Youhui
Abstract : Background and Objectives: Laser is being widely used in clinical treatment nowadays, including 755 nm Alexandrite laser [1, 2]. This study was conducted to examine the clinical outcome of long‐pulse 755 nm Alexandrite laser in the treatment of venous lake of the lip. Study Design/Materials and Methods: Forty‐one patients (2015–2019) were reviewed. The clinical outcomes were assessed 1 month after the treatment. The efficacy of the treatment was classified into four categories: basic recovery (most optimal outcome), effective, improvement, and ineffective (least favorable outcome). Adverse reactions were also recorded. Results: Thirty‐three (80.49%) patients achieved basic recovery and 8 (19.51%) were effective; 29 (70.73%) recovered after receiving one treatment, 3 (7.32%) recovered after receiving two treatments, and 1 (2.44%) recovered after three treatments. Conclusion: Long‐pulse 755 nm Alexandrite laser is an effective treatment for the venous lake of the lip. Lasers Surg. Med. © 2020 Wiley Periodicals LLC